Detailed mark‐up of semi‐monographic legacy taxonomic works using FlorML. Issue 2 (17th March 2014) - Hamann, Thomas D.; Müller, Andreas; Roos, Marinus C.; Sosef, Marc; Smets, Erik
Abstract: We present FlorML, an XML schema, specifically designed for the detailed mark‐up of highly complicated semi‐monographic legacy taxonomic works, such as large Floras and Faunas. We discuss the prerequisites for developing a suitable XML schema, and the limitations presented by the legacy taxonomic works, requirements by stakeholders and the desired output format. Furthermore, we explain how FlorML was deployed to mark up two legacy taxonomic works, Flora Malesiana and Flore du Gabon, how that deployment was improved by the use of the scripting language Perl to automate major parts of the process, and discuss the issues commonly encountered during the mark‐up process. Examples and figures are provided for clarification. Finally, we make suggestions for future research and further developments in the field of biodiversity informatics.